2020
DOI: 10.3390/en13143551
|View full text |Cite
|
Sign up to set email alerts
|

Highly Renewable District Heat for Espoo Utilizing Waste Heat Sources

Abstract: The district heating operator Fortum and the city of Espoo have set a goal to abandon the use of coal in district heating production and increase the share of renewable sources to 95% by the year 2029. Among renewable fuels and heat pumps, waste heat utilization has an important role in Fortum’s plans for the decarbonization of district heating production, and Fortum is considering the possibility of utilizing waste heat from a large data center in its district heating network. The goal of this paper i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…On a more systemic approach, [60] demonstrates that widespread data centre flexibility can support the transition of the Irish electricity system towards 2030 by reducing variable renewable curtailment, carbon emissions, and stability margins. At the district heating/data centre interface, [61] estimate that data centres' waste heat could reduce district heating operation costs by up to 7.3% in Espoo, Finland, and offers a suitable baseload production [62]. Both analyses are based on one-year models without considering the long-term evolution of the district heating system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On a more systemic approach, [60] demonstrates that widespread data centre flexibility can support the transition of the Irish electricity system towards 2030 by reducing variable renewable curtailment, carbon emissions, and stability margins. At the district heating/data centre interface, [61] estimate that data centres' waste heat could reduce district heating operation costs by up to 7.3% in Espoo, Finland, and offers a suitable baseload production [62]. Both analyses are based on one-year models without considering the long-term evolution of the district heating system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In general, a variety of alternatives to decarbonize the energy mix of district heating networks exists. Among others, geothermal [27], biomass [28], waste [29] and heat recovery from industrial excess heat [30] are likely to be the primary heat sources in sustainable district heating networks. Eventually, the increasing cooling demand and the co-design of district heating and cooling networks can also increase the economic viability of these and counteract the reduction of heat density from an economic point of view [31].…”
Section: Genementioning
confidence: 99%
“…The results indicated that the EH tends to increase efficiency in the system, but the implementation of storage is crucial due to the variable nature of the EH availability. Hiltunen et al determined the optimal capacity of EHC required to design a DHS based on EHC, HPs and renewable fuels using scenario analysis in EnergyPRO [112]. The results showed that prioritization of EHC allowed reaching the goal of 95% renewable heat generation.…”
Section: Energypromentioning
confidence: 99%